2013
DOI: 10.7589/2011-12-353
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey for Antibody to Deerpox Virus in Five Cervid Species in Oregon, USA

Abstract: ABSTRACT:Five cervid species in Oregon, USA were tested with a serum neutralization assay for antibody to deerpox virus (DPV). None of the 50 elk (Cervus elaphus ssp. roosevelti and nelsonii) had detectable antibody. Prevalence of antibody to DPV in the remaining species was: 52% (n555) in blacktailed deer (Odocoileus hemionus columbianus), 32% (n5 59) in mule deer (O. hemionus hemionus), and 36% (n550) in Columbian white-tailed deer (O. virginianus leucurus), with an overall antibody prevalence of 40.2% (n516… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The limited morbidity rate registered, are probably due to the origin of the cases collected during passive surveillance. A higher prevalence of PPV and PV infected animals can be supported by serological data that showed high antibody prevalence toward another epitheliotropic virus (DPV), indicating that the exposure to theses pathogens is common but the virulence is low with a consequent low rate of disease in Odocoileus populations (9).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The limited morbidity rate registered, are probably due to the origin of the cases collected during passive surveillance. A higher prevalence of PPV and PV infected animals can be supported by serological data that showed high antibody prevalence toward another epitheliotropic virus (DPV), indicating that the exposure to theses pathogens is common but the virulence is low with a consequent low rate of disease in Odocoileus populations (9).…”
Section: Discussionmentioning
confidence: 90%
“…The first genome sequence of Mule Deerpoxvirus (MDPV), from a farmed white-tailed deer fawn in Florida, has been recently published by Sayler et al (8). A sero-survey, performed in Oregon, indicated that the exposure to DPV is common in Odocoileus populations leading to speculate that the high antibody prevalence and the low rate of observed DPV-related disease may suggest a low virulence of these pathogens (9).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent serosurvey of five cervid species in Oregon, USA, a high prevalence of DPV antibodies was detected in three species from the genus Odocoileus ,whereas none were detected in two elk species ( Cervus spp. ) (Jin et al, 2013). Only two genera were examined in this study, however, the absence of DPV antibodies in the elk species suggests this virus has a restricted host range.…”
Section: Deerpox Virusmentioning
confidence: 99%
“…A number of these granulocytes were actively phagocytizing cellular debris with a myriad of mature virions or free mature virions (Figs. 13,14). In contrast to subacute lesions, large numbers of virions were present only in necrotic dry epidermal cells within the crust of chronic lesions.…”
Section: Transmission Electron Microscopymentioning
confidence: 94%
“…and no detectable antibody in elk (Cervus elaphus). 13 There are 2 pathogenic DPV strains, W-848-83 (W83) and W-1170-84 (W84), whose genomes are 166 and 170 kbp, respectively. The DPV genomes encode several genes that may be involved in regulation of immune responses.…”
mentioning
confidence: 99%